Implementación de un BI para analizar la incidencia de las enfermedades y problemas relacionadas con la salud (CIE-10) en el Ecuador, dentro de los últimos 4 años, utilizando postgresql, matlab y pentaho. - Alvarez Jiménez, Mayra Isabel (2018)
The titling project, proposed by UPS, born from the need to make decisions in the area of health and perform analysis of a large volume of hospital data in connection with the incidence of diseases reported in the various entities of health of Ecuador, the methodology implemented to create the data warehouse is based on the following steps.1) Data download from the web site of the INEC. 2) Analysis and data migration from the statistics application SPSS to PostgreSQL database. 3) Interviews the staff of the INEC, area the ministry of health and doctors, to contribute with ideas for the analysis of the data and the definition of the areas of interest (dimensions) and fact tables. 4) Creation of ETL process (Extract, Transform, and Load). 5) Analysis of the results and generation of materialized views. For the creation of the data warehouse was used the KIMBALL methodology, for the management of the project was used the agile methodology SCRUM, that allows the estimation of the development time of the same, planning partial deliveries of the final product, prioritizing objectives and adapting changes in the course of its development. The platform used consists of the following tools: SPSS, PostgreSQL, Pentaho and Matlab. The present work provides with a tool that allows visualizing the symptoms by criteria as: geographic location, age range, symptom (illness), health entity, period, etc. Allowing visualize the incidence that has each of these criteria of analysis in the Ecuadorian population.